2006
DOI: 10.1111/j.1442-2050.2006.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal replacement in rat using porcine intestinal submucosa as a patch or a tube-shaped graft

Abstract: This study compares the efficacy of porcine intestinal submucosa (SIS) patch graft versus SIS-tube graft in esophageal replacement, using a novel esophageal regeneration model. Clinical function, as well as macroscopic and microscopic morphology were evaluated in both SIS-treated groups. We performed semi-circumferential esophageal excision followed by repair of the defect using either a SIS-patch graft (group I) or segmental esophageal excision followed by a SIS-tube interposition graft (group II) in rats. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 24 publications
(46 reference statements)
3
41
0
Order By: Relevance
“…Previous experiments have shown that circumferential resection of the esophagus and surgical replacement with a collagen tube induced total stricture as early as the first 2 weeks [15,16,17,18]. Such studies have been performed in rats, dogs and piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that circumferential resection of the esophagus and surgical replacement with a collagen tube induced total stricture as early as the first 2 weeks [15,16,17,18]. Such studies have been performed in rats, dogs and piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, circumferential replacement of the esophagus by acellular scaffolds without cell seeding invariably leads to stricture and lack of function. [24][25][26][27][28][29] In patch esophagoplasty models, the addition of muscle cells to the matrix lowers the inflammatory process, accelerates tissue regeneration and restores a better function. 30 Badylak et al 31 showed that covering an acellular scaffold with autologous muscle tissue avoids stricture formation after circumferential esophageal replacement.…”
Section: Article In Pressmentioning
confidence: 99%
“…Cell-free grafts derived from extracellular matrices (ECM) such as decellularized esophagus [12], decellularized urinary bladder submucosa (UBS) [13], acellular dermis [14], gastric acellular matrix [15], small intestinal submucosa (SIS) [1619], decellularized aorta [20] and collagen-based sponges [2124] have been shown to promote host tissue ingrowth and constructive tissue remodeling in a number of animal models of esophageal reconstruction. In addition, small-scale clinical trials have also demonstrated the feasibility of SIS and UBS implants for the repair of esophageal defects [2527].…”
Section: Introductionmentioning
confidence: 99%